Leaf Nutrient Concentrations of Apple Orchards in Isparta Province - İbrahim Erdal (Journal of Agricultural Sciences)
This study was conducted in Isparta province to investigate the mineral nutritional status of apple orchards by means of leaf analysis. For this purpose, seven districts were chosen and ten orchards from each district were selected. Leaf samples were taken during two years from the chosen trees. Leaf analyses results indicated that there was no Mg deficiency in trees. Similarly 97% of orchards did not show N deficiency. The most important nutritional problem was Zn nutrition, and 80% of the orchards showed Zn deficiency. On the other hand, 69, 64, 24 and 11% of the orchards showed P, Ca, K and Mn deficiencies, respectively. Finally, it was concluded that soils were fertilized sufficiently with N, but some important nutritional problems continued. Therefore; special fertilization programs should be applied for other nutrients specially for Zn, P and Ca as well